Puriton attenuates the asthma severity in ovalbumin-induced murine model via balancing Th1/Th2 and inhibiting inflammation - So-Hyeon Bok; Hae Eun Jang; Kwang-Ho Kim; Dae-Hun Park (PLoS ONE, 2025)
In 2019, 262 million asthma patients were estimated, with 455 thousand deaths caused by asthma. It is an incurable chronic inflammatory respiratory disease and is more severe in the elderly and in the young. Forty BALB/c mice were divided into 5 groups of eight mice each: vehicle group (CON), asthma group (OVA), positive drug group (DEX), and Puriton (700 and 1400 μL/head/day). After animal experiment all mice were narcotized for collecting bronchoalveolar lavage fluid (BALF) and blood and then anesthetized for sampling the lungs. White blood cell (WBC) and differential count in BALF and immunoglobulin E (IgE) in serum were measured. Lung tissues were used for histopathological and immunohistopathological studies. Treatment with Puriton decreased the populations of WBC and neutrophil and the level of IgE. It prevented OVA-induced morphological changes in the lung and increased the expression levels of T helper 2 (Th2) cell-related cytokines such as interleukin- (IL-)4, IL-5, and IL-13. It inhibited inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and IL-6. The nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)/ cyclooxygenase-2 (COX-2)/ prostaglandin E2 (PGE2) pathway is a significant inflammatory pathway. Treatment of the subjects with Puriton resulted in the inhibition of the expression of phosphorylated (p)-NF-κB, COX-2, and PGE2 in both the nucleus and cytoplasm. From the results we concluded that Puriton is a promising drug candidate as asthma treatment.